Methicillin-Resistant Staphylococcus aureus Susceptibility Testing by an Automated System, Autobac I - Cleary, Timothy J. (1978)
The Autobac I system was used to evaluate the antibiotic susceptibility pattern of methicillin-resistant Staphylococcus aureus isolates. The results of the Autobac I were compared with the results of the disk diffusion method. The disk diffusion susceptibility pattern showed resistance to methicillin/oxacillin, penicillin, erythromycin, clindamycin, and kanamycin. All isolates were susceptible to cephalothin, chloramphenicol, tetracycline, and gentamicin. There was at least 96% agreement using the Autobac I system with all antibiotics except methicillin and clindamycin. Seventy percent of 57 isolates were recorded as susceptible to methicillin, whereas 9% had an intermediate susceptibility. With clindamycin, 14% were recorded as susceptible and 7% were recorded as intermediate. Upon prolonged incubation of the Autobac I cuvette, the agreement between the two methods was 44% for methicillin and 93% for clindamycin. Changes in the environmental conditions, such as use of 5% sodium chloride broth and a 32°C incubation temperature, did not increase the detection of methicillin-resistant isolates by the Autobac I system.